Magnetohydrodynamic Processes in Solar Plasmas - Srivastava A.K.; Goossens M.; Arregui I. (My University, 2025)
Magnetohydrodynamic Processes in Solar Plasmas provides a comprehensive theory and practice of basic plasma processes in the Sun and heliosphere. It deals with the basic dynamics of the Sun from its interior up to its outer atmosphere in the framework of Magnetohydrodynamics. Topics covered include essential phenomena in the solar interior such as magnetism, dynamos and helioseismology and in the solar atmosphere such as waves, shocks, instabilities, reconnection and coronal heating. The book provides frontline research aspects of solar plasma processes. In addition, the content is relevant for astrophysical plasmas, laboratory plasmas, fluid dynamics and related basic fields. Magnetohydrodynamic Processes in Solar Plasmas not only focuses on the fundamentals of the processes under consideration but in addition it presents recent research developments. In this manner it forms an essential reference for researchers, academics and advanced students in solar physics, astrophysics and related disciplines. © 2024 by Elsevier Inc. All rights reserved, including those for text and data mining, AI training, and similar technologies.